History of Christianity in India, Vol. II: From the Middle of the Sixteenth Century to the End of the Seventeenth Century (1542-1700) - Mundadan, A M (Journal of Dharma, 1983)
Joseph Thekkedath, S.D.B., Ph.D. History of Christianity in India, Vol. II: From the Middle of the Sixteenth Century to the End of the Seventeenth Century (1542-1700). Theological Publications in India (published for Church History Association of India), Bangalore, 1982, xxii +529 pp.